Acquired Cystic Kidney Diseases in Bangladeshi Rural Populations: A Cross- Sectional Investigation - Hasan, Mahmud Javed; Ray, Nitai Chandra; Bari, Muhammad Abdul; Islam, Md Aminul; Ahmed, Sultan (Community Based Medical Journal, 2024)
Acquired cystic kidney disease (ACKD) is a condition characterized by the formation of numerous cysts in the kidneys. It is frequently associated with chronic kidney disease (CKD) and dialysis. Despite its clinical significance, little is known about its prevalence and characteristics among Bangladesh's rural people. Between January and June of 2023, a cross-sectional survey was done with 120 participants from various rural areas of Mymensingh Division, Bangladesh, to observe the prevalence, risk factors, and clinical characteristics of ACKD. Participants were screened for ACKD using ultrasonography. Demographic information, medical history, and pertinent clinical indicators were gathered. Significant connections between ACKD and possible risk variables were identified by statistical analysis. The median dialysis vintage was 33.3 [range:10.6-62.98] months. Renal cysts were seen in 62.5 % (n=74) of participants, 41.6% (n=50) were bilateral. The median [25th-75th percentile] number of cysts in the right kidney was 4 (range: 2-8) and 3 (range: 2-7.3) in the left kidney. ACKD was detected in 29.17% of the study participants. Individuals with a history of CKD and those on prolonged dialysis vintage had significantly greater prevalence. Male populations over 50 years with prolonged dialysis duration were identified as key risk factors for ACKD. ACKD is a significant health hazard in Bangladesh's rural populations, particularly for elderly persons with CKD and those undergoing dialysis. This study aims to investigate the prevalence, clinical characteristics, and associated risk factors of ACKD among rural populations in Bangladesh. Additional longitudinal studies are required to investigate the long-term impact of ACKD on renal function and overall health outcomes in local communities. CBMJ 2024 July: vol. 13 no. 02 P: 218-222